Surface complexation modeling : gibbsite - Karamalidis, Athanasios K. (Wiley, 2010)
This book provides a description of the generalized two layer surface complexation model, data treatment procedures, and thermodynamic constants for sorption of metal cations and anions on gibbsite, the most common form of aluminum oxide found in nature and one of the most abundant minerals in soils, sediments, and natural waters. The book provides a synopsis of aluminum oxide forms and a clearly defined nomenclature. Compilations of available data for sorption of metal cations and anions on gibbsite are presented, and the results of surface complexation model fitting of these data are given.